2006
DOI: 10.1111/j.1525-1497.2006.00536.x
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of medication self-management skill in a low-literacy population

Abstract: BACKGROUND: Patients' ability to manage medications is critical to chronic disease control. Also known as medication management capacity (MMC), it includes the ability to correctly identify medications and describe how they should be taken. OBJECTIVE: To evaluate the effects of low literacy, medication regimen complexity, and sociodemographic characteristics on MMC. DESIGN: Cross‐sectional analysis of enrollment data from participants in a randomized trial. PARTICIPANTS: Patients with coronary heart diseas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
177
6

Year Published

2007
2007
2013
2013

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 211 publications
(191 citation statements)
references
References 23 publications
8
177
6
Order By: Relevance
“…In this study of elderly veterans' medication knowledge, adherence, and adverse drug events, we found a significant association between health literacy and knowledge of the medication name and purpose, as has been shown in other studies (e.g., Kripalani et al, 2006). However, we found no significant association between health literacy and adherence, or between health literacy and ADEs.…”
Section: Discussioncontrasting
confidence: 51%
See 1 more Smart Citation
“…In this study of elderly veterans' medication knowledge, adherence, and adverse drug events, we found a significant association between health literacy and knowledge of the medication name and purpose, as has been shown in other studies (e.g., Kripalani et al, 2006). However, we found no significant association between health literacy and adherence, or between health literacy and ADEs.…”
Section: Discussioncontrasting
confidence: 51%
“…Low health literacy may lead to increased incidence of ADEs through misunderstanding of prescription instructions and warning labels (Davis et al, 2006), incorrect selfadministration (Kripalani et al, 2006), inability to communicate symptoms or signs effectively, or barriers to accessing care for monitoring and evaluation (Murray et al, 2009). Health literacy may also influence outcomes through an effect on medication adherence (Pignone, DeWalt, Sheridan, Berkman, & Lohr, 2005), although studies have shown inconsistent and sometimes contradictory relations (Berkman et al, 2011).…”
Section: H J Mosher Et Almentioning
confidence: 99%
“…Prior findings in HIV treatment found inconclusive results as to the relationship between health literacy and medication adherence. 10,13,[18][19][20] Yet HIV may differ from hypertension. Antiretroviral medications generally have a single manufacturer, and a prior study found that patients with limited literacy often rely on pill characteristics for identification.…”
Section: Discussionmentioning
confidence: 99%
“…6,7 Patients may be non-adherent for many reasons, including forgetfulness, lack of motivation, and barriers such as high drug costs. 8,9 Inadequate health literacy, 2,10-12 poor understanding of the medication regimen, 13 low selfefficacy, 14 and medication regimen complexity can also adversely affect adherence. 15 A number of complex interventions have demonstrated moderate success in enhancing medication adherence.…”
Section: Introductionmentioning
confidence: 99%